Techniques of Satire in Political Speeches - Mohammed Hayder; Hani Kamil Al-Ebadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This paper deals with the techniques of satire which are followed in satire in American political discourse in general and in Trump`s in particular. where these techniques are: irony, paradox, antithesis, enlargement, anti-climax, Exaggeration, and parody. This paper depends on Simpson (2003) model and it picks seven texts to analysis as an example for each techniques of Trump’s political discourse. Also, it gets some results. The satiric speech implies such techniques in order to convey some messages that a speaker would like to be comprehended by the listener. Trump uses all technique in his political discourse.